Differences on the Root and Root Canal Morphologies between Asian and White Ethnic Groups Analyzed by Cone-beam Computed Tomography - Martins, Jorge N R; Gu, Yongchun; Marques, Duarte; Francisco, Helena; Caramês, João (Journal of endodontics, 2018)
Populations from different geographic regions and ethnic backgrounds may present differences in dental morphology. The aim of this study was to compare the differences in root and root canal configurations on Asian and white subpopulations using cone-beam computed tomographic imaging. Information from Asian and white patients was retrieved from 2 cone-beam computed tomographic imaging databases in China and Western Europe. Two calibrated observers collected data regarding the number of roots and Vertucci root canal system configuration for all groups of teeth. A total of 15,655 teeth were analyzed. The z test for independent groups was used to analyze differences between the groups. The significance level was considered at a P value < .05. Reliability tests were performed between observers. Differences were noted in the number of roots per tooth in 6 groups of teeth. The Asian group showed a higher prevalence of single-root configurations in maxillary first premolars (83.2%) and mandibular second molars (45.4%) when compared with whites with 48.7% and 14.3%, respectively. Moreover, 3-rooted configurations in mandibular first molars were more common in Asians (25.9%) compared with whites (2.6%). Seventeen of the 20 analyzed roots had a higher prevalence of Vertucci type I configuration in Asians. Maxillary first molars with second mesiobuccal root canals were more commonly found in whites than in Asians (71.3% and 58.4%, respectively). A similar situation was found in maxillary second molars. The Asian ethnic group presented a higher prevalence of Vertucci type I configuration, whereas the white group displayed a higher number of multiple root canal system morphologies. A clinician should be aware of these differences when treating patients from these ethnic groups.